Inhibition of Chlorination in Streptomyces aureofaciens by Nitriles and Related Compounds - Goodman, Joseph J. (1973)
A number of nitriles and cyano compounds inhibited chlorination by Streptomyces aureofaciens. In most cases, this inhibition was enhanced by bromide. Methylene blue and p-amino-propiophenone reversed the inhibition to some extent.